A robust method to extract the anterior pelvic plane from CT volume independent of pelvic pose. Issue 1 (1st January 2017) - Lee, Changhwan; Kim, Yeesuk; Kim, Hyung Wook; Kim, Young Soo; Jang, Jongseong
Abstract: Purpose: The anterior pelvic plane (APP) is commonly used as a reference plane to assess acetabular orientation. However, conventional methods for determining the APP may not be accurate and are prone to user variability. To overcome these issues, we developed a robust method to accurately extract the APP independent of pelvic pose using three-dimensional pelvic computed tomography (CT). Materials and methods: Twenty-eight studies for suspected nonmusculoskeletal conditions were obtained. The APP was determined by four landmarks that were automatically extracted from user-defined regions of interest (ROIs) with compensation of pelvic pose. The APP defined from these landmarks was quantitatively compared to the APPs determined by an expert and an unskilled. Intraobserver reliability was measured to evaluate the time-interval variability. Finally, we evaluate the robustness of this method to patient posture using an arbitrarily rotated volume. The intraclass correlation coefficients (ICCs) were calculated to determine the interobserver and intraobserver reliabilities. Results: The ICC values for the four landmarks and the APP were similar between the semiautomated method and expert determination (ICC >0.937). The ICC values for intraobserver reliability over time for our method were all 1, demonstrating high reliability. Furthermore, agreement between the parameters determined from the original volume and the rotated volume was nearly perfect. Conclusions: Our method is a useful measurement tool for the APP as it is robust, and the results were similar to an experienced surgeon's determination. Furthermore, it was independent to the direction of the CT slice and more robust than a measurement by an unskilled.